The Theoretical Limits to Redistribution - Roberts, Kevin (Review of Economic Studies, 1984)
This is a revised version of the second Review of Economic Studies Lecture presented in April 1983 at the joint meeting of the Association of University Teachers of Economics and the Royal Economic Society held in Oxford. The choice of lecturer is made by a panel whose members are currently Professors Hahn, Mirrlees and Nobay, and the paper was refereed in the usual way. GEM